(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the spectrum of clinical features of myasthenia gravis at the time of presentation Methods: Forty cases of myasthenia gravis presenting to the Neurology Outpatient Department, Mayo Hospital Lahore were registered. After recording demographic data, their clinical features and functional status were noted and recorded on a specified proforma. Results: Myasthenia gravis, seen roughly equally in both sexes, has a wide range of presentation with various clinical features. The most common initial involvement was ofocular muscles among all followed by bulbar and upper limbs. However facial, lower limb and respiratory muscle involvement was also seen. Conclusion: Myasthenia gravis has a wide spectrum of clinical features. Clinicians ought to be aware of all these features as well as their relative frequencies in order to be able to aptly recognize and diagnose myasthenia gravis early.